A high maneuvering motion strategy and stable control method for tandem twin-rotor aerial-aquatic vehicles near the water surface - Wu, Sifan; Shao, Maosen; Wu, Sihuan; He, Zhilin; Hui Wang; Zhang, Jinxiu; Liu, Yuan (Defence technology, 2025)
The maneuverability and stealth of aerial-aquatic vehicles (AAVs) is of significant importance for future integrated air-sea combat missions. To improve the maneuverability and stealth of AAVs near the water surface, this paper proposed a high-maneuverability skipping motion strategy for the tandem twin-rotor AAV, inspired by the motion behavior of the flying fish to avoid aquatic and aerial predators near the water surface. The novel tandem twin-rotor AAV was employed as the research subject and a strategy-based ADRC control method for validation, comparing it with a strategy-based PID control method. The results indicate that both control methods enable the designed AAV to achieve high stealth and maneuverability near the water surface with robust control stability. The strategy-based ADRC control method exhibits a certain advantage in controlling height, pitch angle, and reducing impact force. This motion strategy will offer an inspiring approach for the practical application of AAVs to some extent.